Propranolol Administration Modulates Neural Activity in the Hippocampal Hilus During Fear Retrieval - Leal Santos, Sofia; Chen, Briana K.; Pereira, Guilherme R.; Pham, Vananh; Denny, Christine A. (Frontiers in Behavioral Neuroscience, 2022)
Altered fear learning is a strong behavioral component of anxiety disorders such as post-traumatic stress disorder (PTSD). Recent efforts have attempted to combine exposure therapies with drugs that target fear memory retrieval and memory reconsolidation, in order to improve treatment efficacy. The noradrenergic (NA) signaling system is of particular interest, due its role in regulating the stress response and its involvement in fear and learning processes. Importantly, propranolol, a non-selective β-adrenergic antagonist that has shown potential in decreasing exaggerated fear in both humans and animal models. In a previous study, we utilized an activity-dependent tagging murine model to determine the neural mechanisms by which propranolol attenuates learned fear. We found that propranolol acutely decreased memory trace reactivation specifically in the dorsal dentate gyrus (dDG), but not in CA3 or CA1. Here, we extended our previous study by investigating whether propranolol additionally altered activity in the hilus, a polymorphic layer that consists of neurons, mossy cells, and GABAergic interneurons. We found that propranolol acutely reduced overall hilar activity in both the dorsal and ventral hilus. Moreover, we report that propranolol significantly altered the activity of parvalbumin (PV)+ cells in the ventral (vDG), but not dorsal DG (dDG). Together, these results suggest that a β-adrenergic blockade may affect the activity of excitatory and inhibitory cell types in hilar layer of the DG, and that these alterations may contribute to manipulating fear memory traces.